1979
DOI: 10.1111/j.1365-2362.1979.tb00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Free insulin, bound insulin, C‐peptide and the metabolic control in juvenile onset diabetics: comparison of C‐peptide secretors and non‐secretors during 24 hours conventional insulin therapy

Abstract: In two groups of juvenile onset diabetics similar in age, weight, diet and daily insulin dosage (eight without C-peptide, group I; eight with C-peptide, group II) the serum levels of free and antibody bound insulin, C-peptide, glucose, lactate, alanine and FFA were determined over 24 h. In addition the affinity and binding capacity of the insulin antibodies were determined in vitro. No correlation was found between free or bound insulin and glucose. This holds true for the individual profiles as well as for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A significant inverse correlation was found between C-peptide and the degree of glycaemic control, as expressed by diurnal mean blood glucose and mean amplitude of glycaemic excursions (MAGE) in patients with the same duration of disease [21]. Comparable results have been obtained in patients with longer durations of disease [35,56,60,61].…”
Section: Metabolic Importance Of Residual B Cell Function At Diagnosimentioning
confidence: 49%
See 2 more Smart Citations
“…A significant inverse correlation was found between C-peptide and the degree of glycaemic control, as expressed by diurnal mean blood glucose and mean amplitude of glycaemic excursions (MAGE) in patients with the same duration of disease [21]. Comparable results have been obtained in patients with longer durations of disease [35,56,60,61].…”
Section: Metabolic Importance Of Residual B Cell Function At Diagnosimentioning
confidence: 49%
“…Several studies have correlated B cell function and insulin-binding antibodies [27,35,[56][57][58] and, except for one study, no significant correlations have been found [35]. In that study the highest titres of antibodies were found in the group without B cell function, but these patients had also had diabetes for longer and were younger at onset.…”
Section: Immune Mechanisms In Relation To B Cell Functionmentioning
confidence: 80%
See 1 more Smart Citation
“…In newly diagnosed, untreated patients with IDDM the peripheral and portal insulin concentrations are, of course, severely reduced. During subcutaneous insulin therapy of IDDM a peripheral hyperinsulinemia is established (23). However, despite a higher insulinemia in peripheral arteries, these diabetics do not have the level of portal vein insulin concentration of normal subjects.…”
Section: Regulation Of Glucose Homeostas1smentioning
confidence: 97%
“…In some studies no better metabolic control was found in patients in whom Cpeptide could be demonstrated [1,2]. Other authors have reported a positive correlation between the degree of metabolic control and C-peptide levels in groups of patients [3][4][5][6][7][8], but in individual patients this relationship was not always present. In almost all studies C-peptide immunoreactivity was measured by methods which include proinsulin bound to insulin antibodies.…”
mentioning
confidence: 99%